PENGAWASAN PEMBAYARAN PAJAK PENGHASILAN (PPh) ORANG PRIBADI BERBASIS PROFESI DALAM UPAYA MENINGKATKAN KEPATUHAN KEWAJIBAN PERPAJAKAN DI KABUPATEN BADUNG - , NI MADE DWIMAYENI SAWITRI, Adrianto Dwi Nugroho,S.H.,Adv.,LL.M. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of research, entitled \"Supervision of Income Taxâs Payment of the Private Person with Professionals-based In Effort to Improve Compliance of Tax Obligations in Badung Regency\" is to know the oversight of individual income tax payments with professional based in Badung regency and the role of tax officer and professional organizations in supervision individual income tax payment of professional services-based professions in Badung. This writing method is empirical research, field research conducted to obtain primary data which is then supported secondary data from the literature research. Then the collected data were analyzed with qualitative methods. The results showed that the Directorate General of Taxation is authorized to supervise one of them by examine the taxâs notification (SPT) data and to request data from third parties such as professional associations and government agencies to adjusting the reporting income âs data of individual taxpayers with independent activities profession-based. Indonesian Tax Consultant Association (IKPI) area of Bali and the Indonesian Notaries Association (INI) Badung Regency is ready to assist Directorate General of Taxation in overseeing the payment of income tax by individual taxpayers profession-based with of course sticking to laws and regulations and existing tax supervision standards process. Dissemination activities undertaken by the Government in collaboration with professional organizations are also expected to add insight or knowledge on taxation of the private person with professions-based.